The Rights of non-Muslims in Islamic Law - Ahmad Dalbahi (UIN Sunan Gunung Djati Bandung, 2013)
Constitutional law in Islam has been protecting the rights of all citizens of either Muslims or non-Muslims. In this study will be discussed several issues relating primarily to the rights of individuals in relation to the rights of citizens, especially Muslims as Muslims progress of individual rights, the right to obtain justice, honor guard in getting fair treatment from the state.